Deploying license-free wireless wide-area networks - Unger, Jack (Cisco, 2003)
Best practices for planning and deployment of broadband WWANs Learn insider tips from an experienced wireless industry leader Understand the principles that underlie the operation of all wireless systems Learn how to provide profitable and reliable wireless Internet access Select the most effective equipment and antenna systems for your area Avoid common pitfalls encountered by new wireless network operators Minimize the effects of noise and interference on your network Enjoy the satisfaction of providing wireless Internet access to your community Practice the business principles used by successful wireless ISPs (WISPs) Use 802.11a, 802.11b, and 802.11g equipment more successfully in your own home, office, or outdoor environment Choose the right network architecture for your wireless network Conduct physical site surveys and radio-frequency (RF) site surveys License-free broadband wireless wide-area networks (WWANs) provide fast deployment of low-cost, high-speed "last-mile" wireless Internet access. License-free wireless technology delivers these benefits without requiring the use of products or services provided by local telephone or cable companies. WWANs enable Internet service providers (ISPs) and corporate IT managers to deploy their own cost-efficient broadband networks that deliver high-speed access for buildings and areas where traditional wired connectivity is either completely unavailable or is cost-prohibitive. Deploying License-Free Wireless Wide-Area Networks is the first book that provides complete, real-world "start-to-finish" design, installation, operation, and support information for wireless ISPs and other organizations deploying outdoor wireless WANs-including coverage of 802.11a, 802.11b, 802.11g, and proprietary-protocol networks. This vendor-neutral book covers all brands of broadband wireless equipment and explains the principles upon which all wireless equipment is based. Inside, you'll find step-by-step instructions and crystal-clear explanations that walk you through initial planning stages and onto full wireless network operation. End-of-chapter review questions reinforce important concepts. Whether you're an IT director, ISP engineer, network architect, or field technician, Deploying License-Free Wireless Wide-Area Networks is your essential reference. With practical, in-depth coverage of the real-world challenges of outdoor, license-free wireless WAN deployment, this book provides a comprehensive, vendor-neutral ...